Village Government Accountability and Transparency in Village Financial Management - Dwi Agus Kurniawan; Banu Witono (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study aims to find out the accountability and transparency procedures of the village government in managing village finances (Study in Karangsari Village, Kutowinangun District, Kebumen Regency). This type of research is a qualitative research with an interactive analysis approach. Data was collected through in-depth interviews, observations and document studies which were then analyzed using an interactive analysis model through four stages, namely (1) Data Collection, (2) Data Reduction, (3) Data Presentation, (4) Conclusion Drawing. The results of the study show that (1) Accountability at the planning, implementation, administration, and financial management reporting stages (2) Transparency of village finances in Karangsari Village in its implementation is guided by the Minister of Home Affairs Regulation Number 20 of 2018. The Karangsari Village Government as the executor of village financial management has carried out the Village Financial Accountability and Transparency process quite well. However, there must be improvements in village financial management and financial accountability by seeking new innovations. And in providing information to the public must be optimized